Effective Permittivity of Biological Tissue: Comparison of Theoretical Model and Experiment. (21st June 2017) - Gun, Li; Ning, Du; Liang, Zhang
Abstract : Permittivity of biological tissue is a critical issue for studying the biological effects of electromagnetic fields. Many theories and experiments were performed to measure or explain the permittivity characteristics in biological tissue. In this paper, we investigate the permittivity parameter in biological tissues via theoretical and experimental analysis. Firstly, we analyze the permittivity characteristic in tissue by using theories on composite material. Secondly, typical biological tissues, such as blood, fat, liver, and brain, are measured by HP4275A Multi-Frequency LCR Meter within 10 kHz to 10 MHz. Thirdly, experimental results are compared with the Bottcher-Bordewijk model, the Skipetrov equation, and the Maxwell-Gannett theory. From the theoretical perspective, blood and fat are regarded as the composition of liver and brain because of the high permittivity in blood and the opposite in fat. Volume fraction of blood in liver and brain is analyzed theoretically, and the applicability and the limitation of the models are also discussed. These results benefit further study on local biological effects of electromagnetic fields.